2010
DOI: 10.1111/j.1399-6576.2010.02219.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive dysfunction and health‐related quality of life after a cardiac arrest and therapeutic hypothermia

Abstract: Half of the patients had a cognitive dysfunction with reduced performance on executive function and episodic memory, indicating frontal and temporal lobe affection, respectively. Reduced performance did not affect HRQOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 41 publications
3
53
0
4
Order By: Relevance
“…Indeed, other authors have also been unable to demonstrate an association with QoL in survivors of cardiac arrest. 21,22 It is likely that for highly functioning individuals, other factors are more influential in QoL perceptions. Therefore, in practice, documenting neurological parameters alone may not be sufficient to assess patient wellbeing; reporting outcomes beyond cognitive function should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, other authors have also been unable to demonstrate an association with QoL in survivors of cardiac arrest. 21,22 It is likely that for highly functioning individuals, other factors are more influential in QoL perceptions. Therefore, in practice, documenting neurological parameters alone may not be sufficient to assess patient wellbeing; reporting outcomes beyond cognitive function should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Despite a good outcome according to the CPC, cognitive difficulties may be prevalent as reported in several smaller studies using neuropsychological tests. 9,10 In a recent review, 30% to 50% of survivors after cardiac arrest were reported to suffer from cognitive impairment. 11 The generalizability of previous studies is poor because of small sample sizes, [12][13][14] missing data, 13,14 and patient selection, that is, the exclusion of those with a poor outcome, 14 inclusion of only patients with severe symptoms, 12 or absence of a nonarrest control group.…”
Section: Clinical Perspective On P 1349mentioning
confidence: 99%
“…23 Another study included 26 patients who had been treated with TH, only evaluating those with a CPC score of 1 or 2, and found that 52% had cognitive dysfunction. 24 Three prospective studies of patients who were not treated with TH found cognitive dysfunction in 42% to 50% of survivors. 12,14,15 Our study cannot define the impact of TH on cognitive outcomes, but it shows that the majority of survivors regain good cognitive function.…”
mentioning
confidence: 99%
“…22 Two small series found that a larger proportion (approximately 50%) of TH-treated cardiac arrest survivors had cognitive impairment. 23,24 One study of 43 patients found that 48% had cognitive impairment, half of whom had "mild" deficits. 23 The Neurobehavioral Cognitive Status Examination (Cognistat) was used for the cognitive screening test.…”
mentioning
confidence: 99%
See 1 more Smart Citation